2003
DOI: 10.1007/s00027-003-0675-4
|View full text |Cite
|
Sign up to set email alerts
|

Role of the photo-Fenton reaction in the production of hydroxyl radicals and photobleaching of colored dissolved organic matter in a coastal river of the southeastern United States

Abstract: Photochemical reactions involving colored dissolved organic matter (CDOM) in natural waters are important determinants of nutrient cycling, trace gas production and control of light penetration into the water column. In this study the role of the hydroxyl radical ( ∑ OH) in CDOM photodegradation was explored as well as the contribution of photo-Fenton chemistry to ∑ OH formation. Photochemically produced ∑ OH was observed under aerobic and dioxygen-depleted conditions in highly colored, acidic natural water sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
149
0
3

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(159 citation statements)
references
References 66 publications
6
149
0
3
Order By: Relevance
“…If enough Fe(II) is present to be oxidized to Fe(III) from photo-Fenton chemistry, which consumes H 2 O 2 , OH radical production also could result in CDOM photobleaching (White et al 2003). At the pH range of our samples (7-8) this process is enhanced and might in part explain the trends in H 2 O 2 production we observed during the UDOM photobleaching experiment.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…If enough Fe(II) is present to be oxidized to Fe(III) from photo-Fenton chemistry, which consumes H 2 O 2 , OH radical production also could result in CDOM photobleaching (White et al 2003). At the pH range of our samples (7-8) this process is enhanced and might in part explain the trends in H 2 O 2 production we observed during the UDOM photobleaching experiment.…”
Section: Discussionmentioning
confidence: 77%
“…Del Vecchio and Blough (2002) found a decrease in efficiency of direct and indirect photobleaching with increasing wavelengths, yet greater relative photobleaching at longer wavelengths. Moreover, CDOM photobleaching is a function of iron availability and photochemistry (Gao and Zepp 1998;White et al 2003). Osburn and Morris (2003) suggested that CDOM photoreactivity can increase with salinity across an estuarine gradient, but Minor et al (2006) found a decrease in CDOM photobleaching at 280 nm when humic CDOM was added to an artificial salinity gradient used to mimic coastal mixing.…”
mentioning
confidence: 99%
“…, approximating a summer day as 6 h of noontime sunlight) have been observed upon irradiation with sunlight or simulated sunlight of waters with sufficiently high Fe and low pH to make HO· production by Fenton's reaction likely (see Table 2 in White at al. 2003).…”
Section: Discussionmentioning
confidence: 99%
“…It is also documented that estuarine iron is usually positively correlated with river flow and particulate loading (e.g. Lippiatt et al, 2010) and that its complexation with DOM can greatly affect photochemical reactions in estuarine systems (Gao and Zepp, 1998;White et al, 2003). These potential variations in the chemical nature of CDOM would certainly add to the variation of AQY in coastal systems and may not be directly related to salinity.…”
Section: Seasonal Changes In Photoproduction Efficiencymentioning
confidence: 99%
“…The absorption of solar radiation by CDOM can lead to a whole host of chemical reactions, including formation of reactive oxygen species such as hydroxyl radical (OH q ) and superoxide (O − 2 ) (Micinski et al, 1993;Moffett and Zafiriou, 1993;Zika et al, 1985;Blough and Zepp, 1995), breakdown of large organic molecules into lower molecular weight carbon compounds (Wetzel et al, 1995;Kieber et al, 1989Kieber et al, , 1990, alteration of the redox state of biologically important metals (White et al, 2003;Barbeau, 2006;Barbeau et al, 2003), and formation of oxidized inorganic carbon species, such as CO and CO 2 (measured as DIC) (Clark et al, 2004;Johannessen and Miller, 2001;Miller and Zepp, 1995;White et al, 2010;Ziolkowski and Miller, 2007;Wang et al, 2009;Xie et al, 2004;Zafiriou et al, 2003). On an annual global basis, photoproduction of these two carbon compounds may be almost equal to oceanic new production (∼10 15 moles C yr −1 ; Johannessen, 2000;Wang et al, 2009).…”
Section: Introductionmentioning
confidence: 99%